The Changing Face of Dental Licensing Examinations - Mark L. Christensen (Taylor & Francis Group, 2023)
ABSTRACTRecent developments have changed characteristics of the examinations required for licensing as a dentist in most U.S. jurisdictions. These include implementation of the INBDE that now has replaced Part I and Part II of the National Board Dental Examination, the recent merger of regional testing agencies, and the arrival of ADEX as a single national clinical examination with almost universal results portability. Simulation is rapidly replacing clinical procedures previously performed for patients. The DLOSCE and Interstate Compacts portend further change for dental regulation. Together, these developments now make the dental licensing examination notably different than has been experienced by most licensees.